PENGARUH LIABILITAS DAN STRUKTUR MODAL TERHADAP PROFITABILITAS: (Studi Empiris Pada Perusahaan Sub Sektor Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia Periode 2019-2020) - Dwi Urip Wardoyo; Hani Nur Aini; Jihan Septiani Putri Kusworo (Jurnal Publikasi Ekonomi dan Akuntansi, 2022)
Profitability is the ability of a company to obtain profits related to sales, total assets, or capital. This ratio is used to assess the company's ability to get the highest possible profit from the overall assets owned so that investors are interested in investing in the company. The purpose of this study was to determine the simultaneous and partial effect of liabilities and capital structure on profitability in the food and beverage sub-sector listed on the Indonesian stock exchange for the 2019-2020 period. The method used in this study is a quantitative method. The type of research in this research is descriptive. The sampling technique in this study used a purposive sampling technique using company sample panel data for a period of two years so that 48 samples were obtained. This research uses panel data method using SPSS software. The results showed that partially liabilities had a significant effect on profitability and capital structure had a significant effect on profitability.